Interferensi Bahasa Ibu Terhadap Penguasaan Berbicara Bahasa Arab Mahasiswa PBA Semester II - rahayu, Puji (Al-Fathin: Jurnal Bahasa dan Sastra Arab, 2024)
This article aims to discuss the speaking errors of second semester students of the Arabic Language Education Study Program at STAINU Kotabumi Lampung. As students in Lampung who have various cultures and languages as their mother tongue and then switch to Arabic as a foreign language (B2), students still often make mistakes when speaking Arabic. So that errors in transferring B1 to B2 occur due to several factors, namely: different cultural backgrounds, choice of word errors, and following word order as in the mother tongue (B1). The type of research used is a qualitative research method with data sources namely simple conversations of STAINU Kotabumi students, as well as observation and documentation data collection techniques. The results of the research show: mother tongue interference in learning to speak Arabic for STAINU Kotabumi Lampung students in the second semester covering phonology, morphology and syntax.